Intratumoral CD103+CD4+ T cell infiltration defines immunoevasive contexture and poor clinical outcomes in gastric cancer patients. (1st January 2020) - Gu, Yun; Chen, Yifan; Jin, Kaifeng; Cao, Yifan; Liu, Xin; Lv, Kunpeng; He, Xudong; Lin, Chao; Liu, Hao; Li, He; He, Hongyong; Qin, Jing; et al.
ABSTRACT: Our previous study has identified intratumoral CD103 + CD8 + T cells as a favorable prognostic factor in gastric cancer. However, the significance of CD103 + CD4 + T cells in gastric cancer hasn't yet been elucidated. Here, we aimed to investigate the clinical significance and phenotype characteristics of intratumoral CD103 + CD4 + T cells in gastric cancer. In our study, 469 formalin-fixed and paraffin-embedded samples and 24 fresh tissue specimens of patients with gastric cancer from Zhongshan Hospital were included. We manifested that intratumoral CD103 + CD4 + T cells in gastric cancer predicted poor overall survival and inferior responsiveness to fluorouracil-based ACT. The density and phenotypic characteristics of CD103 + CD4 + T cells in gastric cancer were detected by immunohistochemistry and flow cytometry, which showed that CD103 + CD4 + T cells exhibited an immunosuppressive phenotype and higher retention capacity in tumor tissues. Furthermore, increased CD103 + CD4 + T cells contributed to CD8 + T cell dysfunction with decreased granzyme B (GZMB), interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α) and perforin (PRF-1) expression in gastric cancer. Overall, this study revealed that intratumoral CD103 + CD4 + T cell infiltration defined immunoevasive contexture and predicted poor prognosis and inferior responsiveness to fluorouracil-based ACT. Therefore, we recommended that CD103 + CD4 + T cells might be a potential immunotherapeutic target for gastric cancer.